Advertising and New Narrative: Linearity to Transmediality - Avogadro-Thomé, Marisa (2016)
Our environment has changed. We live in a real and virtual society, where new Information and Communications Technology (ICT) offers us various possibilities of information generation and transmission, getting through geographical and cultural barriers and crossing the world in record time. The digital revolution is not over and the media ecosystem as a consequence has not stabilized yet. The increasing use of media and ICT has put traditional media in crisis within the transformation of the Advertising industry context and the alternative funding and business practices. Therefore, this article presents a critical analysis on Advertising and the new narratives, trying to find adequate bibliographical support to study the path from linearity to transmediality.